2023
DOI: 10.1111/1541-4337.13237
|View full text |Cite
|
Sign up to set email alerts
|

Dry fractionation process operations in the production of protein concentrates: A review

Manoj Kumar Pulivarthi,
Rania Marie Buenavista,
Sneh Punia Bangar
et al.

Abstract: The market for plant proteins is expanding rapidly as the negative impacts of animal agriculture on the environment and resources become more evident. Plant proteins offer competitive advantages in production costs, energy requirements, and sustainability. Conventional plant‐protein extraction is water and chemical‐intensive, posing environmental concerns. Dry fractionation is an energy‐efficient and environmentally friendly process for protein separation, preserving protein's native functionality. Cereals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The latter cereals can also be processed to render oil, β-glucan, or arabinoxylan. In general, dry and wet milling are commonly employed by the grain industry to fractionate grains or pulses into their constituents of protein, starch, and fiber [9,[22][23][24][25][26][27][28][29]. Dry milling uses different types of mills, air classifiers, and electrostatic separators to break down and fractionate grains or pulses into flours and ingredients [9,22], while wet milling applies wet extraction methods to separate protein, starch, and fiber from grains [24,26,28,29].…”
Section: Characterization and Fractionation Of Grainsmentioning
confidence: 99%
See 3 more Smart Citations
“…The latter cereals can also be processed to render oil, β-glucan, or arabinoxylan. In general, dry and wet milling are commonly employed by the grain industry to fractionate grains or pulses into their constituents of protein, starch, and fiber [9,[22][23][24][25][26][27][28][29]. Dry milling uses different types of mills, air classifiers, and electrostatic separators to break down and fractionate grains or pulses into flours and ingredients [9,22], while wet milling applies wet extraction methods to separate protein, starch, and fiber from grains [24,26,28,29].…”
Section: Characterization and Fractionation Of Grainsmentioning
confidence: 99%
“…Studies have shown that wet milling is obsolete and uneconomical, with intensive uses of water and energy [34,47]. On the other hand, dry milling has shown great potential as a sustainable system for the separation of protein, starch, fiber, and other ingredients [9,22,27]. In this respect, a hybrid model would improve the efficiency of wheat milling and fractionation by minimizing waste and reducing water consumption, in addition to improving the quality of fractions and ingredients.…”
Section: Sustainable Grain Processing Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, also for rapeseed deoiling is strongly advised to improve the milling yield, reach sufficient disclosure of protein bodies from the cells and to enable consecutive electrostatic separation. Furthermore, it is recommended to aim for ambient milling conditions unless the lower temperature is desired to preserve volatile compounds (Pulivarthi et al, 2023).…”
Section: Pre-treatment Affecting Milling and Subsequent Dry Separationmentioning
confidence: 99%